"Does the poor matter" in pro-poor driven sub-Saharan African cities? towards progressive and inclusive pro-poor tourism. Issue 3 (15th August 2019) - Musavengane, Regis; Siakwah, Pius; Leonard, Llewellyn
Abstract : Purpose: The purpose of this paper is to question the extent to which Sub-Saharan African cities are progressing towards promoting pro-poor economies through pro-poor tourism (PPT). It specifically examines how African cities are resilient towards attaining sustainable urban tourism destinations in light of high urbanization. Design/methodology/approach: The methodological framework is interpretive in nature and qualitative in an operational form. It uses meta-synthesis to evaluate the causal relationships observed within Sub-Saharan African pro-poor economies to enhance PPT approaches, using Accra, Ghana, Johannesburg, South Africa, and Harare, Zimbabwe, as case studies. Findings: Tourism development in Sub-Saharan Africa has been dominantly underpinned by neoliberal development strategies which threaten the sustainability of tourism in African cities. Research limitations/implications: The study is limited to three Sub-Saharan African countries. Further studies may need to be done in other developing countries. Practical implications: It argues for good governance through sustainability institutionalization which strengthens the regulative mechanisms, processes and organizational culture. Inclusive tourism approaches that are resilient-centered have the potential to promote urban tourism in Sub-Saharan African cities. These findings contribute to the building of strong and inclusive Institutions for Sustainable Development in the Sub-Saharan African cities to alleviate poverty. Social implications: These findings contribute to the building of strong and inclusive institutions for sustainable development in the Sub-Saharan African cities to alleviate poverty. Originality/value: The "poor" are always within the communities, and it takes a community to minimise the impact of poverty among the populace. The study is conducted at a pertinent time when most African government's development policies are pro-poor driven. Though African cities provide opportunities of growth, they are regarded as centres of high inequality.